2020
DOI: 10.1098/rsif.2019.0878
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering complex central autonomic networks at rest: a functional magnetic resonance imaging study on complex cardiovascular oscillations

Abstract: This study aims to uncover brain areas that are functionally linked to complex cardiovascular oscillations in resting-state conditions. Multi-session functional magnetic resonance imaging (fMRI) and cardiovascular data were gathered from 34 healthy volunteers recruited within the human connectome project (the ‘100-unrelated subjects' release). Group-wise multi-level fMRI analyses in conjunction with complex instantaneous heartbeat correlates (entropy and Lyapunov exponent) revealed the existence of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 125 publications
(220 reference statements)
1
47
0
Order By: Relevance
“…These findings support the role of thalamus, insula and putamen in autonomic control, as shown in previous studies (17,20,30,53), and add roles for the temporal gyrus whose role in cardiac regulation has been recently suggested (29,37). Despite the well-established association of activity in amygdala with heart rate fluctuations in task-based experiments (17, 54), no association was observed here.…”
Section: Discussionsupporting
confidence: 93%
“…These findings support the role of thalamus, insula and putamen in autonomic control, as shown in previous studies (17,20,30,53), and add roles for the temporal gyrus whose role in cardiac regulation has been recently suggested (29,37). Despite the well-established association of activity in amygdala with heart rate fluctuations in task-based experiments (17, 54), no association was observed here.…”
Section: Discussionsupporting
confidence: 93%
“…7 Knowledge of their interconnectivity and function associated with specific regions continues to evolve. 8,9 Recent functional MRI analyses from SUDEP cases, in addition to people with epilepsy considered at higher risk, have shown altered connectivity between autonomic cortical and subcortical cardiac and respiratory regulatory regions, including the thalamus, suggesting disorganization of interconnections. [10][11][12][13] Structural MRI analyses from large data sets (ENIGMA-epilepsy consortium) recognize stereotypical regional patterns of cortical thinning in epilepsy syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…A group of supratentorial brain regions involved in autonomic modulation and control of brainstem centers has been referred to as the central autonomic network (CAN) 7 . Knowledge of their interconnectivity and function associated with specific regions continues to evolve 8,9 . Recent functional MRI analyses from SUDEP cases, in addition to people with epilepsy considered at higher risk, have shown altered connectivity between autonomic cortical and subcortical cardiac and respiratory regulatory regions, including the thalamus, suggesting disorganization of interconnections 10‐13 …”
Section: Introductionmentioning
confidence: 99%
“…In humans, functional neuroimaging studies have demonstrated activation of the hippocampus during sympathetic challenges 31 as well as negative correlations of parasympathetic HRV with hippocampal activity 30 and with the grey matter volume of the parahippocampal gyrus 33 . A recent neuroimaging investigation 40 has reported a negative correlation between the activity in the hippocampus and an HRV complexity index which decreases with sympathetic activation 41 .…”
mentioning
confidence: 99%